Coated tool for hot stamping of coated or uncoated metal sheets and method for producing same - Patents.com
Patent Information
- Application Number
- JP2021544521
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-01
- Filing Date
- 2020-02-03
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-02-03
Smart Images

Figure 0007635713000001 
Figure 0007635713000002 
Figure 0007635713000003
Abstract
Description
[Technical field]
[0001] The present invention relates to coatings applied to the surfaces of tools, particularly forming tools (also referred to herein as dies). These tools, also known as hot stamping, are used for press hardening of AlSi or Zn coated and uncoated metal sheets, e.g. ultra high strength steels (UHSS), the most common type being 22MnB5 USIBOR. The WorldAutoSteel format is used herein to define different types of steel, such as UHSS, AHSS, or LSS. Metallurgical type, minimum yield strength (MPa), and minimum tensile strength (MPa) are used herein to distinguish different types of steel. Generally, steels with yield strength levels above 550 MPa and tensile strengths above 780 MPa are referred to as UHSS. Forming tools are tools or machine accessories that are shaped to give a predetermined contour or profile to a workpiece, whereby the workpiece is reshaped without adding or removing material and without changing its mass. The present invention further relates to a method of applying the coating of the present invention to a substrate. [Background technology]
[0002] The use of advanced high-strength steels (AHSS) and UHSS in the automotive industry has been steadily increasing over the past decades. AHSS are a series of high-strength steels that contain microstructural phases other than ferrite, pearlite, or cementite, e.g., martensite, bainite, austenite, and / or retained austenite, in sufficient amounts to produce unique mechanical properties. Most AHSS have a multiphase microstructure and typically their yield strength levels exceed 550 MPa. The use of such types of steels in the manufacture of structural parts of automobiles (e.g., the so-called "body-in-white" (BIW) or chassis) significantly reduces the overall weight of the automobile. As in this case, said structural parts can be manufactured using thinner metal sheets while maintaining a high level of strength. Since UHSS have a considerably higher absorption of impact energy compared to low-strength steels (LSS), the obvious advantage is the manufacture of automobiles that consume less fuel and are safer in the event of an accident. LSS are a group of steels that exhibit a tensile strength below 270 MPa, examples of which include non-interstitial mild steels.
[0003] However, forming UHSS and AHSS metal sheets is difficult and results in heavy wear of the forming dies, especially continuous abrasive and / or adhesive wear of the dies, e.g., heavy material transfer from the metal sheet to the die surface. In both cases, the quality of the manufactured parts is significantly affected. Frequent maintenance intervals of the forming dies are necessary to maintain the quality of the manufactured parts. The initiation and propagation of fatigue cracks in the dies can significantly shorten the life of the expensive dies. This results in reduced productivity and excessive manufacturing costs.
[0004] When using cold forming processes, one way to minimize damage to the tool is to use different surface treatments, which can improve the performance of the forming tool. One of the most common and industrially practical techniques is to use various nitriding methods, such as plasma or low pressure nitriding, to harden the surface of the tool. This is done via the diffusion of nitrogen into the subsurface region of the steel, which results in an improved resistance to abrasive wear and, in many cases, also to adhesive wear. Furthermore, the resistance to fatigue cracks is improved by introducing compressive stresses into the surface. The compressive stresses arise from the volume change due to the introduction of nitrogen and / or carbon, and from thermal effects. As an alternative solution, several hard and wear-resistant coatings based on nitrides, carbides, oxides, or combinations thereof have been developed and used industrially. The use of these coatings alone or in combination with nitriding solutions could significantly improve the performance of forming tools used in the cold forming of, for example, uncoated HSS and UHSS steel sheets, or metal sheets with a lesser total strength to be achieved (for example, lower than 1000 MPa).
[0005] Plannja, Sweden, has introduced a forming process called press hardening or hot stamping, which is used, for example, for forming coated sheet materials or for forming sheet materials in general, and the achieved total strength is higher than 1000 MPa (for example, 1000MPa-2000MPa or 1250MPa-2000MPa). In this kind of forming process, incandescent hot steel sheets are simultaneously formed and quenched in the same die. The whole forming process, including the quenching step, takes place in a few seconds, for example, 8-12 seconds. As a result of such rapid quenching of hot-formed product parts, a martensitic structure is formed, which shows a total strength of up to 2000 MPa. In the past few years, the use of such press hardened steel (PHS) parts in the automotive industry, for example, A&B pillars, bumpers, roof and rocker rails, tunnels, etc., has increased dramatically from 3 million pieces in 1987 to 250 million pieces in 2015.
[0006] Compared with the cold forming process, the advantages of using the hot stamping process are: - Elimination of springback typically seen in cold stamped AHSS plates, -One-step molding process, -Excellent weldability of PHS parts due to the use of low carbon alloys, It is.
[0007] In order to prevent corrosion of the PHS parts, the plate material is usually coated with AlSi or Zn coating before carrying out the hot stamping process.
[0008] However, the use of this process creates several difficulties. The level of adhesion and abrasive wear of the die in the hot stamping process is significantly higher than that occurring in the cold forming process. One reason is the high forming temperature of about 800°C and the very high quenching rate of more than 27 degrees / second. What this means is that the sheet undergoes a very fast temperature change (e.g., from a temperature of about 800°C or higher to a temperature of about 150°C within about 20 seconds), while during this temperature change, the sheet remains in contact with the die (forming tool) used to form it. It is believed that the high forming temperature results in contact between the die and the semi-molten AlSi or Zn coating of the coated sheet (e.g., USIBOR plate), leading to considerable material transfer from the sheet to the die surface. Also, the high quenching rate leads to the formation of a very hard AlSiFeO layer on the surface of the manufactured part, which causes abrasive wear of the die. Another common damage mode of coated dies in the hot stamping process is a process called galling. Galling is a type of wear caused by adhesion between sliding surfaces. When materials gall, parts of the material are pulled at the contacting surfaces, especially if there is a large force compressing the surfaces together. Galling is caused by a combination of friction and adhesion between the surfaces, followed by slippage and tearing of the crystalline structure. Galling initially leads to a buildup of material on the forming tool and eventually spalling of the accumulated material, including parts of the forming tool, such as parts of the coating. Summary of the Invention [Problem to be solved by the invention]
[0009] There is a need to find a solution to sufficiently increase the resistance of the forming tool to abrasive and adhesive wear at temperatures above 800°C, especially above 700°C, to perform the hot stamping process while avoiding failure of the forming tool. As there are coatings that increase the resistance to abrasive wear over a certain temperature range, there are also coatings that increase the resistance to adhesive wear over a specific temperature range. However, it is difficult to find a coating that has high resistance to abrasive and adhesive wear at temperatures above 800°C, especially above 700°C.
[0010] The object of the present invention is to provide a solution for improving the performance of forming tools used in hot stamping, in particular for forming tools used in the hot stamping of AlSi and Zn coated or uncoated sheet materials (such as USIBOR plate), thereby increasing the tool life. [Means for solving the problem]
[0011] The present invention proposes to provide a coating for use in coating forming tools intended for use in hot forming processes as claimed in claim 1.
[0012] The present invention discloses a coating system that provides enhanced adhesive and abrasive wear resistance, applied to substrates such as, but not limited to, steel substrates, particularly those used as forming tools suitable for press hardening processes. The coating system of the present invention is a multi-layer system. It is composed of at least one upper layer (hereinafter also referred to as the upper multi-layer nanolayer, top layer, or layer 5, as shown in Figures 1 and 5), including but not limited to CrN, TiAlN, and VCN. The top layer is characterized by a minimal carbon content with respect to the nitrogen content, taking into account the carbon and nitrogen content profile throughout that layer. This top layer is primarily intended to provide galling resistance. The coating system of the present invention may include additional layers, particularly at least one layer to provide the necessary load-bearing capacity required to withstand the combined mechanical load and thermal shock during the forming and quenching steps in the hot stamping process.
[0013] Generally, the coating can be provided with further layers to achieve further improvements regarding different coating properties such as adhesion to the substrate, cohesion within the coating structure, hardness (HIT) and elastic modulus (EIT). Furthermore, the coating must be able to withstand the temperatures typically encountered during hot forming processes as mentioned above. Therefore, some tests were carried out at temperatures that can typically occur in hot stamping processes (temperatures between 800°C and 950°C), as shown in the various tests.
[0014] The coating system of the present invention is preferably deposited using PVD techniques, such as cathodic arc or magnetron sputtering. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic diagram of one embodiment of a coating system according to the present invention. [Diagram 2]FIG. 2 is a schematic diagram of one possible method of depositing an embodiment of a coating system according to the present invention. [Diagram 3] On the left is a scanning electron microscope (SEM) micrograph of a coating according to the invention taken with a BSE, and on the right is an in-lens detector SEM micrograph of a coating according to the invention. [Figure 4] FIG. 13 is a schematic showing a PVD coated sphere vibrating within an AlSi layer on a USIBOR sheet during a high temperature SRV test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The coating system of the present invention is presented to be applied to the forming tools used in press hardening. The coating is either a single layer or a multi-layer coating, which is then deposited on the surface of the substrate (e.g., the steel substrate associated with the forming tools and forming members). The coating system of the present invention includes at least one layer (referred to herein as the top layer or layer 5).
[0017] The top layer itself (layer 5 in FIG. 1) is a multilayer (also called top multilayer), preferably a multi-nanolayer system (also called top layer stack in the context of the present description). The top layer stack is composed of at least three different types of layers. For example, a layer of type A, a layer of type B and a layer of type C are deposited to form a sequence of "...A / B / C / A / B / C / A...".
[0018] According to a preferred embodiment of the invention, a top layer stack is deposited and formed of a type A layer comprising primarily chromium nitride or consisting of chromium nitride (CrN), a type B layer comprising primarily titanium aluminum nitride or consisting of titanium aluminum nitride (TiAlN), and a type C layer comprising primarily vanadium carbonitride or consisting of vanadium carbonitride (VCN).
[0019] Particularly good results have been achieved by using a coating of the present invention having a top layer stack including layers of CrN, TiAlN, and VCN.
[0020] Therefore, the top stack is preferably designed to have layers A, B, and C of CrN, TiAlN, and VCN, respectively.
[0021] In such a case, preferably the layer of the topmost stack closest to the substrate is a layer comprising CrN, followed by a layer comprising TiAlN, followed by a layer comprising VCN.
[0022] However, the present invention should not be construed as being limited to the preferred embodiments described herein.
[0023] The top layer stack of the coating system of the present invention must include at least one layer set, which in the context of the present invention should be understood as a sequence formed of three monolayers: one A layer, one B layer, and one C layer, deposited in succession.
[0024] It is important to note that by successively depositing monolayers A, B, and C as described above, an interface can be formed between two monolayers deposited in contact with each other. Such an interface between two monolayers can contain elements of both the two monolayers. For example, by depositing a layer B on a layer A, it is possible to form a kind of interfacial layer between the respective layers A and B, containing elements from layers A and B. It will depend on the type of coating process used to deposit the top layer stack.
[0025] Preferably, and particularly preferably, when the thicknesses of the monolayers A, B and C are in the nanometer range, the top layer stack should comprise more layer sets, typically from 25 to 600 layers. The total coating thickness of the top layer stack should be in the range of 0.5 μm to 12 μm, preferably in the range of 2 μm to 7 μm.
[0026] The inventors have found that the coating of the present invention, including the above-mentioned top layer, exhibits very good properties in terms of abrasive and adhesive wear resistance. Furthermore, the inventors have observed that the composition of the top layer is very important in achieving optimal performance in terms of resistance to material transfer from the AlSi or Zn layer on the USIBOR sheet to the tool surface. In this sense, the carbon content is determined by the coexistence of both load resistance and maximum abrasive wear resistance.
[0027] To improve adhesion between the top layer and the substrate of the forming tool, an adhesion layer (herein referred to as layer 1) can be deposited on the substrate. The adhesion layer comprises CrN, preferably consists of CrN. It is preferably a single layer and is deposited directly on the substrate. The thickness of this CrN-containing layer is selected to be between 100 nm and 3 μm, preferably between 300 nm and 1.5 μm.
[0028] The performance of the coating system of the present invention can be improved even further by depositing an additional layer comprising CrN and TiAlN. That layer (referred to herein as layer 2, or second multilayer - see FIG. 1) is a multilayer and can also be a multi-nanolayer system (referred to herein as CrN / TiAlN stack). The CrN / TiAlN stack, which is preferably deposited on layer 1, or that layer can also be deposited directly on the substrate surface. Preferably, layer 2 is deposited starting with a layer comprising CrN, preferably consisting of CrN. On top of that layer comprising CrN, another layer comprising TiAlN is deposited. That layer comprising TiAlN preferably consists of TiAlN. The CrN / TiAlN stack can include one or more sets formed of two layers, one consisting of CrN and one consisting of TiAlN.
[0029] In other words, the CrN / TiAlN stack includes at least one CrN / TiAlN set, but is not limited to one CrN / TiAlN set. To form a layer (layer 2) including CrN and TiAlN, preferably 5 to 130 sets are deposited. The thickness of layer 2 can range from 150 nm to 4 μm, and is preferably selected to be between 600 nm and 3 μm. This layer is known to exhibit good load-bearing capacity (meaning the ability to support a load applied to a substrate).
[0030] The inventors have found that the coating of the present invention, which not only comprises layer 5 but also layers 1 and 2 as described above, is highly suitable for stamping processes. Forming tools coated in this way can generally exhibit superior wear resistance in hot stamping processes compared to state-of-the-art coatings.
[0031] The resistance of the coating to abrasive and adhesive wear can be further improved by adding two more layers to the system (referred to herein as Layer 3 or third multilayer, and Layer 4 or fourth multilayer). Surprisingly, the inventors have discovered that within this system, it is beneficial to add a layer (Layer 3) that includes V and deposit it on Layer 2.
[0032] Layer 3 is a nanolayer system (referred to herein as CrN / TiAlN / VN stack) comprising at least CrN, TiAlN, and VN. The CrN / TiAlN / VN stack is composed of a set of three layers, which are deposited on top of each other (see FIG. 1). Of the at least three layers, the layer comprising CrN is closest to the substrate. This layer preferably consists of CrN. On top of this layer, a layer comprising TiAlN is deposited, which preferably consists of TiAlN. On top of this layer, a layer comprising VN is deposited, which preferably consists of VN. To form the coating system of the present invention, at least one set is used to form layer 3. However, this is not a limitation. Typically, between 4 and 80 sets are deposited to form a layer comprising CrN, TiAlN, and VN. The thickness of the layer can range from 20 nm to 4 μm, and is preferably selected to be between 800 nm and 3 μm.
[0033] Layer 4 is also a multi-layer system constructed like layer 3, but with incremental addition of carbon to change the VN layers to VCN layers, i.e., at the bottom of layer 4, it exhibits a low carbon content, while at the top of layer 4, it exhibits a high carbon content. The inventors have found that by adding such a type of layer between layers 3 and 5, further improvements in wear resistance can be achieved.
[0034] Layer 4 is a nanolayer system (referred to herein as CrN / TiAlN / VN stack) including at least CrN, TiAlN, and VN, with the carbon gradually added to change the VN layer into a VCN layer. The CrN / TiAlN / VCN stack is composed of a set of three layers, which are deposited on top of each other (see FIG. 1). Of the at least three layers, the layer including CrN is closest to the substrate. This layer is preferably made of CrN. On top of this layer, a layer including TiAlN is deposited, which is preferably made of TiAlN. On top of this layer, a layer including VCN is deposited, which is preferably made of VCN. At least one set is used to form layer 3 to form the coating system of the present invention, but this is not a limitation. Typically, between 4 and 80 sets are deposited to form a layer including CrN, TiAlN, and VCN. The thickness of the layer can range from 20 nm to 4 μm, and is preferably selected to be between 800 nm and 3 μm.
[0035] The inventors have also observed that the coating of the present invention works best if the substrate of the forming tool has been pre-nitrided. The nitriding process can be carried out either in the same deposition chamber or in a separate deposition chamber.
[0036] To clarify the layering of the coating system of the present invention, it will now be described by means of embodiments. The embodiments of the present invention are described by way of examples, which are meant to be merely illustrative and therefore non-limiting.
[0037] According to one preferred embodiment of the invention shown in FIG. 1, the multi-layer system consists of five different layers deposited on the substrate of the forming tool. A CrN layer (called layer 1 in this embodiment) is deposited directly on the substrate. On top of layer 1, a layer consisting of CrN and TiAlN (called layer 2 in this embodiment) is deposited. On top of layer 2, a layer consisting of CrN, TiAlN and VN (called layer 3 in this embodiment) is deposited. On top of layer 3, a layer consisting of CrN, TiAlN and VCN with a gradient carbon content profile (called layer 4 in this embodiment) is deposited on layer 3. The top layer (called layer 5 in this embodiment) consists of CrN, TiAlN and VCN with a constant carbon content throughout the layer. The total thickness of the coating described in this embodiment ranges from 4 μm to 20 μm.
[0038] The sum of the coating thicknesses of layers 4 and 5 preferably comprises 40% to 50% of the total coating thickness, but is not limited to this amount. As can be seen, layers 4 and 5 are carbonitride layers.
[0039] Layer 4 is a transition layer from a pure nitride layer (layer 3) to a carbonitride layer (layer 5). Thus, as the distance of layer 4 from the substrate increases, the level of carbon increases and the level of nitrogen decreases across the thickness of layer 4. In this regard, layer 4 is a transition layer from a pure nitride layer (layer 3) to a carbonitride layer (layer 5). a Ti b Al c V d ) λ (C x N y ) δwhere x and y are preferably adjusted as follows: 0≦x≦0.33 and 0.67≦y≦1. The ratio of metals (i.e., the sum of the contents of Cr, Ti, Al, and V) to nonmetals (i.e., the sum of the contents of C and N) is preferably selected to be 0.72≦λ / δ≦1.27. Also, the contents of the individual metal elements Cr, Ti, Al, and V are preferably selected as follows: 0.20≦a≦0.30, 0.05≦b≦0.15, 0.15≦c≦0.25, and 0.40≦d≦0.50, and a+b+c+d=1, preferably 0.20≦a≦0.30, b=0.10, c=0.20, and 0.40≦d≦0.50, and a+b+c+d=1.
[0040] Layer 5 is (Cr a Ti b Al c V d ) λ (C x N y ) δ where 0.4≦x / y≦0.6 and 0.65≦λ / δ≦1.1, preferably x / y=0.5 and λ / δ=0.72. The contents of the individual metallic elements Cr, Ti, Al, and V are selected as follows: 0.20≦a≦0.30, 0.05≦b≦0.15, 0.15≦c≦0.25, and 0.40≦d≦0.50, preferably a=0.20, b=0.10, c=0.20, and d=0.50.
[0041] Layers 1, 2, and 3 are compound nitride layers. These layers are stoichiometric nitrides with a metal to nonmetal ratio of 1.
[0042] To deposit the coating system described in this embodiment, three different target materials were used in an Oerlikon Balzers INNOVA deposition chamber, as shown in FIG. 2: Cr, TiAl, and V. In addition to the Cr and V elemental target materials, a TiAl target was metallurgically prepared in powder form with an Al to Ti weight ratio of about 2. Pure nitrogen gas was present in the chamber to generate layers 1 to 3. At the transition to layer 4, acetylene gas was additionally fed into the chamber. The flow rate of acetylene was gradually increased while keeping the level of nitrogen gas constant. Acetylene gas is very reactive, so the gas needs to be introduced into the chamber as close as possible to the substrate to be coated. Since the aim was to generate a high carbon content in the coating, the acetylene gas was released in the immediate vicinity of the substrate. The same applies to O (oxygen), which is also highly reactive. However, the situation is different for N (nitrogen), which is less reactive than acetylene gas and can therefore be introduced into the chamber without such a special arrangement. The method resulted in a gradient layer 4, starting as a pure nitride and ending as a carbonitride. The acetylene gas flow was kept constant throughout layer 5 so that a carbonitride layer with constant composition was formed as the top layer. A negative substrate bias of 60 V was used throughout the first three layers to form a coating with the desired structure and properties. The negative substrate bias was increased to 100 V during gradient layer 4 and remained constant at -100 V throughout layer 5.
[0043] In the framework of the present invention, the properties and structure of the coating solution described in this embodiment have been tested. Scanning electron microscope (SEM) micrographs taken by conventional and in-lens methods are shown in FIG. 3. On top of the bottom layer 1, a dense and featureless CrN layer, a nanolayer of CrN / TiAlN is deposited. The hardness (HIT) and elastic modulus (EIT) of this layer are about 27 GPa and 300 GPa, respectively. The bilayer period of this nanolayer is measured to be 35 nm. In layer 3, a nanolayer of CrN / TiAlN / VN is deposited. The mechanical properties of this layer are measured to be 29 GPa for HIT and 340 GPa for EIT. The total thickness of all three nanolayers combined is estimated to be 55 nm. Finally, the top C-containing layers, layers 4 and 5, have a HIT of 24 GPa and an EIT of 250 GPa, respectively. The presence of C in these two layers results in a refinement of the nanolayer structure such that the thickness of the three CrN / TiAlN / VCN layers is reduced in half to about 22 nm.
[0044] The resistance of the coating to adhesive wear, defined as the migration and build-up of AlSi or Zn from the coated USIBOR sheet to the surface of the PVD coating, is measured at high temperatures of about 730°C in an SRV tester by an innovative test method. In this innovative method, a 100Cr6 steel ball with a diameter of 10 mm was coated with the PVD coating of the present invention. As a counterpart, a round AlSi-coated USIBOR sheet cut to a diameter of 21 mm was fixed in a holder suitable for use at high temperatures. The USIBOR sheet was then heated via a resistance heating table in contact with the sheet holder. The temperature of the incandescent USIBOR sheet was measured at 730°C via a secondary thermocouple, compared to the set temperature of 900°C in the SRV tester. The temperature of 730°C achieved on the USIBOR sheet is high enough to bring the AlSi layer to a semi-liquid level, which is consistent with the actual practice in industrial applications and is suitable for the study of build-up resistance. To represent the real conditions of AlSi-USIBOR hot stamping applications, the test parameters such as the contact time between the ball and the USIBOR sheet, the normal load applied to the ball and its vibration frequency were adjusted in a way that ensured that the coated ball was always inside the depth of the AlSi layer and never in contact with the underlying 22MnB5 steel. A normal load of 10 N was used to meet the above requirements. The contact time between the coated ball and the AlSi-coated USIBOR plate was set to 1 min before the next cycle began. A schematic diagram of the performed test is shown in Figure 4. This is done to simulate the contact of the coated tool with a new piece of metal plate in a real hot stamping application. A 3D confocal nanofocus microscope was then used to measure the volume and height of the AlSi buildup on any PVD coating to quantitatively and qualitatively evaluate the buildup resistance of that coating. Depending on the performance of the tested coating, this process could be repeated up to 20 times on the same spot of the coated ball, after which nanofocus microscope measurements were made.Using this unique test method, the coatings of the present invention demonstrated orders of magnitude less build-up volume compared to conventional state-of-the-art AlCrN and TiAlN coatings deposited by the same PVD process.
[0045] The resistance of the coating to abrasive wear was measured using a high temperature pin-on-the-disk tester. The maximum temperature achieved in this test was 800°C. For this, the PVD coating of the present invention was applied to a round Inconel piece suitable for high temperature measurements. Once the temperature was reached, a polishing ball with a diameter of 6 mm made of aluminum oxide was brought into contact with the PVD-coated Inconel specimen. The linear velocity of the ball and the total contact time with the coated specimen were 2.64 cm / s and 10 min, respectively. Finally, a 3D confocal nanofocus microscope was used to measure the profile of the racetrack, allowing the wear that had occurred on the PVD coating of interest to be measured.
[0046] 1. A coated substrate having a coating that provides enhanced abrasive and adhesive wear resistance, the coating having a multilayer structure including a multilayer deposited as an upper multilayer, the upper multilayer being formed by sublayers of types A, B and C, the three sublayers being stacked alternately with one another forming a sequence of types ...A / B / C / A / B / C / A... - the type A sublayer is a chromium nitride layer, the type B sublayer is a titanium aluminium nitride layer, - Type C sublayer is a vanadium carbonitride layer A coated substrate comprising: A coated substrate as described in the preceding paragraphs, characterized in that the substrate is a forming tool.
Claims
1. A coated tool for hot stamping of coated or uncoated metal sheets, comprising:
1. A coated tool, comprising: a tool substrate having a coated substrate surface in contact with the coated or uncoated metal plate, the coating on the coated substrate surface being a multi-layer coating comprising one or more lower layers and an upper layer, the lower layer being deposited closer to the substrate surface than the upper layer, the upper layer being an upper multi-layer; - said upper layer is designed to provide galling resistance; a top layer (layer 5) is deposited having a multi-nanolayer structure formed by sub-layers of type A, B and C, the three sub-layers being deposited alternately with each other to form a sequence of the type ...A / B / C / A / B / C / A..., and at least two layer sets are deposited, each layer set consisting of a stack of three nanolayers, consisting of one A nanolayer, one B nanolayer and one C nanolayer, to form said multi-nanolayer structure; where the type A nanolayer is composed of at least 90 at% chromium and nitrogen, - the nanolayer of type B is composed of at least 90 at% titanium, aluminum and nitrogen; - type C nanolayers are composed of at least 90 at% vanadium, carbon and nitrogen, and a coated tool, characterized in that the layer thickness of said upper layer (layer 5) is between 0.5 μm and 15 μm.
2. 2. A coated tool according to claim 1, characterized in that the sum of the layer thicknesses of the three nanolayers A, B and C forming a sequence is between 15 nm and 300 nm.
3. In the upper layer (layer 5), (Cr a Ti b A c V d ) λ (C x N y ) δ When considering the average chemical element composition in atomic percentages expressed as: The average composition is measured taking into account a layer thickness extension of at least 100 nm, the coefficients a, b, c, and d correspond to the composition ratios of Cr, Ti, Al, V, C, and N, respectively, in the ranges of 0.20≦a≦0.30, 0.05≦b≦0.15, 0.15≦c≦0.25, and 0.40≦d≦0.50, and a+b+c+d=1 and x+y=1; 3. Coated tool according to claim 1 or 2, characterized in that the coefficients λ and δ are coefficients describing the stoichiometry and 0.72≦λ / δ≦1.
27.
4. 4. Coated tool according to claim 3, characterized in that in the upper layer (layer 5), the average ratio (x / y) of the carbon content to the nitrogen content can be considered constant since it varies by less than 10% of the maximum value along the entire thickness of the upper layer (layer 5).
5. 5. A coated tool according to any one of claims 1 to 4, characterized in that in the upper layer (layer 5), an interface is formed between two sublayers deposited in contact with each other, said interface containing elements of both of the two sublayers.
6. 6. A coated tool according to any one of claims 1 to 5, characterized in that the upper multilayer comprises from 25 to 600 layers, the total coating thickness of the upper multilayer being in the range of from 0.5 μm to 12 μm.
7. an adhesion layer is deposited directly on the substrate, between the upper multilayer and the substrate; A coated tool according to any one of the preceding claims, characterized in that the adhesion layer comprises CrN.
8. a second layer is deposited on the substrate between the upper multilayer and the substrate; A coated tool according to any one of the preceding claims, characterized in that the second layer comprises CrN and TiAlN.
9. 9. The coated tool of claim 8, wherein the second layer comprises 5 to 130 sets formed of one layer of CrN and one layer of TiAlN, and the thickness of the second layer ranges from 150 nm to 4 μm.
10. 10. Coated tool according to claim 8 or 9, characterized in that a third layer is deposited on the second layer, said third layer being a nanolayer system comprising at least CrN, TiAlN and VN.
11. 11. The coated tool of claim 10, wherein the third layer comprises 4 to 80 sets to form a third layer comprising CrN, TiAlN and VN, and the thickness of the third layer ranges from 20 nm to 4 μm.
12. 12. The coated tool of claim 10 or 11, wherein a fourth layer is deposited over the third layer, the fourth layer being a transition layer from a nitride layer to a carbonitride layer, the fourth layer having an increasing level of carbon and a decreasing level of nitrogen across a thickness of the fourth layer as the distance of the fourth layer from the substrate increases.
13. The fourth layer is made of (Cr a Ti b A c V d ) λ (C x N y ) δ is a compound of x and y are adjusted so that 0≦x≦0.33 and 0.67≦y≦1; the ratio of the sum of the contents of metals, in particular Cr, Ti, Al and V, to the sum of the contents of non-metals, in particular C and N, is selected such that 0.72≦λ / δ≦1.27; 13. The coated tool of claim 12, wherein the contents of the individual metal elements Cr, Ti, Al, and V are adjusted such that 0.20≦a≦0.30, 0.05≦b≦0.15, 0.15≦c≦0.25, and 0.40≦d≦0.50, and a+b+c+d=1.
14. The upper multilayer is made of (Cr a Ti b A c V d ) λ (C x N y ) δ A carbonitride compound having a constant composition, wherein 0.4≦x / y≦0.6 and 0.65≦λ / δ≦1.1; 14. The coated tool according to claim 1, wherein the contents of the individual metallic elements Cr, Ti, Al and V are selected such that 0.20≦a≦0.30, 0.05≦b≦0.15, 0.15≦c≦0.25 and 0.40≦d≦0.
50.
15. A method for producing a coated tool according to any one of claims 1 to 14, comprising the steps of: A method comprising coating a surface of a substrate using a PVD process.
16. - pre-nitriding said substrate in a deposition chamber; - when producing any of layers 1, 2, and / or 3, pure nitrogen gas is present in the deposition chamber and a negative substrate bias of 60V is used; - when producing optional layer 4, additional acetylene gas is supplied to the deposition chamber, the nitrogen gas level is kept constant, the acetylene flow rate is gradually increased, and the negative substrate bias is increased from 60V to 100V; - keeping the flow of acetylene gas constant through the top multilayer, a carbonitride layer of constant composition is formed as the top multilayer, and a negative substrate bias of 100V is kept constant; 16. The method of claim 15, wherein the step of:
Citation Information
Patent Citations
Article coated with oxidation and wear resistant film
JP1996296064A
Hard laminated coating film, hard laminated coating film coated tool and formation of the hard laminated coating film
JP2002275618A
Press forming die, and method for manufacturing press forming die protection film
JP2012232344A
Hard film and metal mold
JP2017110248A
Covering member with excellent sliding properties
WO2013047548A1